P84 Defining a primary composite outcome from hospital episode statistics data to test the benefit of cardiac magnetic resonance (cmr) imaging after primary percutaneous coronary intervention (ppci). (2nd September 2017) - Pufulete, M; Harris, J; Dorman, S; Brierley, R; Reeves, B
Abstract : Background: We researched the feasibility of using routinely collected data to establish a registry to document the use of cardiac magnetic resonance imaging (CMR) in patients with suspected heart attack who activate the primary percutaneous coronary intervention (PPCI) pathway. To compare outcomes between patients having CMR or not, we aimed to define a primary composite outcome, representing clinically important changes in management resulting from CMR, using data from Hospital Episode Statistics (HES) or the Patient Episode Database Wales (PEDW). Clinically important changes in management, and patient subgroups to which these related, were defined by formal consensus. Methods: Patients at four UK sites were prospectively consented. We assembled a database by linking hospital-collected data about the index PPCI admission (demography, clinical, biochemistry and imaging) and CMR 'exposure' within 10 weeks with HES/PEDW data for the following 12 months. An experienced medical coder identified ICD10 diagnostic codes and OPCS procedure codes that the pre-defined clinically important changes in management achieved by CMR were hypothesised to influence. Episodes in HES/PEDW inpatient, outpatient and accident and emergency datasets with these codes were identified. This process was applied to key patient subgroups: i) PPCI; ii) multivessel coronary disease; iii) out-of-hospital cardiac arrest; iv) coronary angiogram showing unobstructed arteries. Results: Of the 1670 patients consented, 1476 (88%) had PPCI; 682 (41%) had multivessel disease, and 194 (12%) had unobstructed arteries. 189 (11%) had CMR within 10 weeks of the index admission. 1612 (97%) had their index event identified in HES/PEDW and 985 of these (61%) had a full year of follow-up available. Focusing on important changes by patient subgroup avoids creating a composite outcome based on diverse changes. Frequencies of relevant health episodes will be reported for patient subgroups and by CMR exposure. Comparing frequencies is straightforward but identifying better targeting of care to patients' needs without a change in frequency, e.g. due to better diagnostic accuracy of CMR, is complex. Discussion: Clinical events relating to important changes in management resulting from CMR can be identified in HES but CMR may not alter the frequency of these events. This case study demonstrates the promise of using routinely collected data to evaluate changes in practice. However, it is challenging to identify subtle changes in management such as better targeting of care without changing its frequency. In future, imaging investigations and changes in management should be identified more accurately by linking to the Diagnostic Imaging Dataset and prescribed medications.